PARTISIPASI MASYARAKAT TERHADAP CAGAR ALAM SEBAGAI BENTUK PELESTARIAN LINGKUNGAN UNTUK WARISAN MANUSIA DI MASA DEPAN - Wahyu Tri Hartanto (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2023)
The natural environment has a very important role in sustaining human life, it makes nature and humans go hand in hand. The exploited ability of nature possessed by humans can affect the state of nature as desired. The influence generated by this act of exploitation does not only have an impact on present life, but also on future life. Massive acts of exploitation are carried out on the basis of commercialized personal interests. This will cause concern in itself because it will disturb the balance of natural ecosystems, especially for plants and animals which should be given legal and direct protection as a conservation effort.